2021
DOI: 10.1021/acs.jafc.0c07450
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Development of Novel Chimeric Lysins with Highly Specific Inhibition against Salmonella by Computer-Aided Design

Abstract: Four novel chimeric lysins (P361, P362, P371, and P372), which were the fusion of Salmonella phage lysins and novel antimicrobial peptide LeuA-P, were obtained using bioinformatics analysis and in silico design. The recombinant chimeric lysins were expressed in E. coli BL21(DE3) strain and showed highly specific inhibition against Salmonella. The minimal inhibitory concentrations (MICs) of P362 and P372 to S. typhi CMCC 50071 were 8 and 16 μg/mL, respectively. Both 1 × MIC P362 and P372 could increase the oute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…NPN is a hydrophobic fluorescent dye that cannot penetrate into intact cells. Once the OM is damaged, NPN enters the hydrophobic environment of the cell membrane, accompanied by an increase in the fluorescence intensity . As shown in Figure A, both Ce(1–8) and CL5 were able to penetrate the OM of E.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…NPN is a hydrophobic fluorescent dye that cannot penetrate into intact cells. Once the OM is damaged, NPN enters the hydrophobic environment of the cell membrane, accompanied by an increase in the fluorescence intensity . As shown in Figure A, both Ce(1–8) and CL5 were able to penetrate the OM of E.…”
Section: Resultsmentioning
confidence: 94%
“…The changes in the OM permeability induced by the peptides were investigated by the NPN uptake assay E.…”
Section: Methodsmentioning
confidence: 99%
“…Another study demonstrated improved activity of chimeric variants of a Salmonella phage lysin when fused with novel antimicrobial peptides generated from leucocin A. The enhanced anti- Salmonella typhi ( S. typhi ) activity in infected chickens helped in their increased shelf life ( Nie et al, 2021 ). Adding cationic and hydrophobic peptides to lysins is another efficient method to generate novel effective lysin candidates, such as Lysep3.…”
Section: Engineering and Formulation Strategies To Improve The Lytic ...mentioning
confidence: 99%
“…In contrast, the application of endolysins against Gram-negative bacteria is still limited due to the presence of an outer membrane that obstructs direct access to PG [ 19 , 20 , 21 ]. Nevertheless, relevant studies have demonstrated that some endolysins are capable of breaking through the outer membrane barrier effect of Gram-negative bacteria with the help of outer-membrane permeabilizers (OMPs) [ 21 ], cationic peptides [ 22 ], or antimicrobial peptides [ 23 ]. An attractive strategy is the use of endolysins or endolysin-antimicrobial peptide fusion proteins that can eliminate the protective effect of the outer membrane and lyse bacteria without pretreatment with other OMPs.…”
Section: Introductionmentioning
confidence: 99%
“…An attractive strategy is the use of endolysins or endolysin-antimicrobial peptide fusion proteins that can eliminate the protective effect of the outer membrane and lyse bacteria without pretreatment with other OMPs. For instance, Nie et al generated antimicrobial peptide-endolysin chimeric proteins that were able to break through the outer membrane of Salmonella and kill these Gram-negative bacteria with high specificity and efficiency [ 23 ]. In addition, Guo et al identified and characterized endolysin LysPA26 that has strong bactericidal activity against MDR Pseudomonas aeruginosa without pretreatment with OMPs [ 24 ].…”
Section: Introductionmentioning
confidence: 99%